Perception and Possibilities of ICT Tools in the Education from the Teachers' Perspective - Klement, Milan; K. Bártek; Jiří Dostál (Univerzita Palackého v Olomouci, 2017)
A constant development of information and communication technologies, including their introduction into the education, place more and more demands on teachers who have to be prepared to work with modern ICT tools and to create suitable educational materials for the needs of teaching designed in this fashion.The submitted publication reacts on those topical calls, and it strives for an overall analysis of ways and approaches to the employment of ICT tools by the teachers of pre-primary, basic and secondary schools in the area of realization of teaching supported by modern didactic means and digital technologies.
Keywords: Pedagogika